Vorsorgeuntersuchungen und Check-ups in der Kardiologie - Rudolph, Ulrike; Laufs, Ulrich (DMW - Deutsche Medizinische Wochenschrift, 2019)
Cardiovascular diseases (CVD), especially coronary artery disease (CAD), are the leading causes of morbidity and mortality worldwide. Elimination of modifiable risk factors has the potential to prevent up to 80 % of CVD. Therefore, disease prevention is based on the assessment of individual total CVD risk by using risk scores such as SCORE-algorithm that include the known main cardiovascular risk factors such as age, sex, smoking status, arterial hypertension und cholesterol.
Keywords: kardiovaskuläres Risiko; nichtinvasive kardiologische Diagnostik; nichtsymptomatische Personen; bildgebende Diagnostik; Prävention kardiovaskulärer Erkrankungen